Exploring the influence of media and social factors on altruistic behavior using the general learning model and norm activation theory - Chi-Horng Liao (Scientific Reports)
Abstract Altruism is beneficial to society as it promotes mental and physical health alongside economic and societal growth. Previous studies have indicated, however, that people tend not to engage in altruistic behaviors toward strangers. Therefore, it is crucial to investigate the factors that motivate individuals to participate in altruistic actions. This study explores the dynamic interplay of media and social factors that enhance altruistic behavior in adults, utilizing the General Learning Model (GLM) and Norm Activation Theory (NAT). To achieve this, the Decision-Making Trial and Evaluation Laboratory (DEMATEL) approach, coupled with Structural Equation Modelling (SEM), is applied. The research comprehensively examines the direct and indirect influence of media elements (such as prosocial media content and persuasive communication) and social factors (including religiosity and social norms) on altruistic behavior. Empathy, moral elevation, and compassion serve as mediators in this process. The DEMATEL approach involves a panel of 20 experts, while SEM analyzes data from a significant sample of 1296 participants drawn from the general public in Taiwan. DEMATEL results shed light on causal factors shaping altruistic behavior, highlighting the roles of religiosity, empathy, and compassion. Shifting to the SEM results, most direct relationships between variables are statistically significant, affirming their importance. However, the findings also reveal unexpected negative associations, challenging the initial hypotheses. Notably, compassion and persuasive communication were found to have negative correlations with altruistic behavior, contrary to expectations.